The persistent Colombian conflict: Subnational analysis of the duration of violence (2012)
Focusing on the Colombian armed conflict, this paper develops for the first time a within-country analysis of violence duration. It examines a wide range of factors potentially associated with violence duration at the municipal level for the period 1988-2004, including geographic factors, economic and social variables, institutional characteristics, victimization variables and government intervention. It individuates the most robust correlates of the persistence of localized conflict, both across specifications and using different econometric models of duration analysis. Results suggest that violence in Colombia is more persistent in places where illegal rents are available. Better quality institutions and a more active military are in turn associated with shorter conflict episodes. © 2012 Copyright Taylor and Francis Group, LLC.